2016
DOI: 10.1159/000451084
|View full text |Cite
|
Sign up to set email alerts
|

Positive CD63 Basophil Activation Tests Are Common in Children with Chronic Spontaneous Urticaria and Linked to High Disease Activity

Abstract: Background: The basophil activation test (BAT) using CD63 expression is a sensitive and specific tool for the diagnostic workup of autoimmune chronic spontaneous urticaria (CSU). The definition of a positive BAT is directly dependent on the reference range and the cutoff values established in control populations. As of now, the pediatric reference range and cutoff values of the CD63 BAT remain to be established. Methods: In this study, we analyzed CD63 expression in 80 children (1-17 years old) without chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 31 publications
1
44
0
2
Order By: Relevance
“…Tryptase blood levels are considered to be a selective marker of mast cell activation, 4 while tetraspanin (CD63) is a cell surface marker that is upregulated on degranulating basophils and mast cells, and can be measured by flow cytometry. 5,6 There were no substantial changes in tryptase/CD63 5 levels assessed at the same time (tryptase 40-35 lg/L and CD63 1.8-1.7%; normal range < 1.8% 5 ). The patient was asymptomatic without disease flares within 1 month following treatment initiation.…”
Section: Reportmentioning
confidence: 83%
See 1 more Smart Citation
“…Tryptase blood levels are considered to be a selective marker of mast cell activation, 4 while tetraspanin (CD63) is a cell surface marker that is upregulated on degranulating basophils and mast cells, and can be measured by flow cytometry. 5,6 There were no substantial changes in tryptase/CD63 5 levels assessed at the same time (tryptase 40-35 lg/L and CD63 1.8-1.7%; normal range < 1.8% 5 ). The patient was asymptomatic without disease flares within 1 month following treatment initiation.…”
Section: Reportmentioning
confidence: 83%
“…In addition, we assessed changes in the levels of two biomarkers related to mast cell activation: tryptase and CD63. Tryptase blood levels are considered to be a selective marker of mast cell activation, while tetraspanin (CD63) is a cell surface marker that is upregulated on degranulating basophils and mast cells, and can be measured by flow cytometry . There were no substantial changes in tryptase/CD63 levels assessed at the same time (tryptase 40–35 μg/L and CD63 1.8–1.7%; normal range < 1.8%).…”
Section: Reportmentioning
confidence: 97%
“…BATs assess histamine release or upregulation of activation markers of donor basophils in response to stimulation with the serum of CSU patients. BATs can help to co‐assess disease activity in patients with urticaria as well as to diagnose autoimmune urticaria . Furthermore, BAT can be used as a marker for responsiveness to ciclosporin A or omalizumab …”
Section: Diagnosis Of Urticariamentioning
confidence: 99%
“…The detection of autoantibodies in children does not affect the prognosis . Recently, it was found that positive CD63 basophil activation test is common in PcsU and is associated with high disease activity . Low blood basophil counts on the contrary were linked to earlier symptoms resolution …”
Section: Possible Causes/triggers Of Chronic Urticariamentioning
confidence: 99%